The Influence of Multi-frequency Current Injection in Image Reconstruction for Two-Dimensional High-Speed Electrical Impedance Tomography (EIT) - Aris Widodo; Agus Rubiyanto; Endarko Endarko (IPTEK The Journal of Engineering, 2019)
The image reconstruction for two-dimensional high-speed Electrical Impedance Tomography (EIT) has been successfully studied with multi-frequency current injection. The aim of this study is to get the best image reconstruction under the influence of multi-frequency current injection of this EIT system. In this method, we used current injection at 1 mA with varies of frequency in the range 10 to 50 kHz injected at the practical phantoms with 16 electrodes. Polyvinyl chloride (PVC) cylinder was put in the practical phantom as the anomaly. Then, The boundary voltage of the practical phantom was measured by the voltage measurement circuit. After that, it processed in the computer with Gauss-Newton Algorithm to got image reconstruction. The result showed that the best image reconstruction was achieved at 10 kHz of frequency current injection. The best image reconstruction had more accuracy of shape, position and electrical properties of an anomaly in boundary phantom than another image reconstruction result.